Synthesis of Binary Ti-Si Mixed Oxides Nanoparticles with Rutile Structure as Selective Catalyst for Epoxidation of Alkenes - F. Farzaneh (Journal of Sciences, Islamic Republic of Iran)
The nanoparticles of Ti-Si mixed oxides (NTSO) with Rutile structure were prepared by sol-gel method in a mixture of alcohol and water as solvent. The solid product was characterized by XRD, FTIR, SEM, TEM, UV, TGA and laser Raman spectroscopy. The catalytic activity of NTSO (5-10 nm) was investigated in the epoxidation of cis stilbene, trans stilbene, and norbornene by using oxidants such as tert-butylhydroperoxide (TBHP), molecular oxygen (O2)/isobutyraldehyde (IBA) and hydrogen peroxide (H2O2). It was found that epoxides of trans-stilbene andnorbornenewereformedquantitativelywiththegreenH2O2oxidantduring12h.